Negative plasmon dispersion in 2H-NbS2 beyond the charge-density-wave interpretation. (26th October 2016) - Cudazzo, Pierluigi; Müller, Eric; Habenicht, Carsten; Gatti, Matteo; Berger, Helmuth; Knupfer, Martin; Rubio, Angel; Huotari, Simo
Abstract: We examine the experimental and theoretical electron-energy loss spectra in 2 H - Cu 0.2 NbS2 and find that the 1 eV plasmon in this material does not exhibit the regular positive quadratic plasmon dispersion that would be expected for a normal broad-parabolic-band system. Instead we find a nearly non-dispersing plasmon in the momentum-transfer range q < 0.35 Å −1 . We argue that for a stoichiometric pure 2 H -NbS2 the dispersion relation is expected to have a negative slope as is the case for other transition-metal dichalcogenides. The presence of Cu impurities, required to stabilize the crystal growth, tends to shift the negative plasmon dispersion into a positive one, but the doping level in the current system is small enough to result in a nearly-non-dispersing plasmon. We conclude that a negative-slope plasmon dispersion is not connected with the existence of a charge-density-wave order in transition metal dichalcogenides.